Kritik Terhadap Konsep Negara Ideal AL Farabi Serta Relevansinya Dengan Era Modern - Muhammad Azrul Amirullah; Ilma Tsaqila Khoirun Nisa; Aulia Habibi; Muhammad Mardani (Universitas Islam Negeri Islam Kiai Ageng Muhammad Besari Ponorogo, 2025)
Abstract: Al-Madinah al-Fadhilah or what is called the ideal state is a concept of government initiated by a Muslim scholar named Al Farabi. The concept has an orientation towards achieving the highest happiness of society through cooperation, justice, and wise leadership that directs society towards common goals, not individual interests, by using normative approaches and qualitative research this research can produce a critical analysis of the concept of Al Farabi who initiated the concept of al-Madinah al-Fadhilah by mixing the realm of philosophy which of course many of these things are not understood for its implementation in the present day which in the end, the concept of al-Madinah al-Fadhilah is more appropriately understood as a political ideal rather than an applicable government system. The system functions as an ideal moral standard for evaluating every existing political system and behind the concept that was initiated there are shortcomings because the concept is very philosophical so it is difficult for today's society to understand, basically the concept of the ideal state of Al-Farabi is heavily influenced by Greek philosophy and Islamic theology, which makes it tend to be theoretical and difficult to realize in the real practice of state life. To determine whether the concept proposed by Al Farabi is still relevant or contradictory, the author has entitled this article: